Gastroesophageal Reflux Disease-related Symptom Assessment in Subjects with Malignant Dysphagia Receiving Esophageal Stents. Issue 12 (December 2014) - North, D. Alan; Schlegel, Melissa; Martin, Robert C. G.
Concerns remain over the ability to stent across of the lower esophageal sphincter (LES) for esophageal adenocarcinoma and the effects of gastroesophageal (GE) reflux. Thus, the aim of this study was to demonstrate minimal quality-of-life (QOL) side effects in patients undergoing esophageal stenting across the LES. An Institutional Review Board–approved prospective clinical trial evaluated the results of the Gastrointestinal Symptom questionnaire that includes a validated GE reflux disease (GERD) assessment (GERD-HRQL) and a dysphagia assessment. Consecutive patients were enrolled in this clinical trial, with 81 per cent male, 19 per cent female, median age of 62 years, with adenocarcinoma of the GE junction as their diagnosis. The median dysphagia score was 3 (only liquids can be tolerated) prestent and was improved to a median score of 0 (ability to eat all foods) poststent ( P = 0.01). The median GERD score was 0 (none) prestent and did not change with a median score of 0 (none) poststent ( P = 0.2). All GERD-related questions were unchanged prestent and poststent in all categories, specifically: frequency of GERD, time of day of reflux, pain behind breastbone, and pain medications. There was also no difference in regurgitation frequency (median prestent 1 vs poststent 0, P = 0.08), texture (prestent 2 [semisolid] vs poststent 1 [liquid]). There was only a statistical change in the ability to belch (prestent 0 [no ability] to poststent 1 [ability]), P = 0.02) and the ability to vomit. Esophageal stenting across the GE junction for dysphagia relief in esophageal malignancies does not adversely effect a patient's QOL in regard to reflux-related symptoms.